Variação interanual da composição das assembléias de peixes em quatro micro-bacias do nordeste paraense - Bastos, Douglas Aviz (Instituto Nacional de Pesquisas da Amazônia - INPA, 2013)
The Amazon Basin is the largest fluvial system on Earth, being formed by countless small streams regionally known as “igarapés”. These streams can show high variability in local conditions between each other because they occur under different climatic, topographic, phytophysiognomic, and biogeographic configurations. This combination of factors affects the composition of stream fish communities, since it varies with the microhabitat complexity promoted by structural characteristics of small streams. Another important factor affecting stream fish composition is the temporal variability of environmental conditions. Studies taking into account all these aspects were scarcely conducted in the Amazon Basin, being mainly restricted to fish communities of the Central Amazon. The eastern portion of the Amazon Basin was even less investigated, which may represent a critical research gap considering that this region has been historically facing high levels of anthropic pressures. The present study aimed to evaluate the effects of environmental factors and their temporal variation on stream fish communities in four sub-basins of the northeastern Amazon, Pará state. We observed significant differences of species diversity and abundance among sub-basins and years. Environmental characteristics were not clearly distinct among sites or years, however, they had strong relation with fish species composition. Another objective of this study was to present a list of fish species from the northeastern Amazon. We registered seven new occurrences for the region and 23 new species. This result is surprising given that the studied region has the longest history of human colonization in the Amazon, with a significant amount of species inventories. We believe that our study brings important information for the faunal knowledge of the region and for the management and conservation of fish species from small Amazonian streams, an ecosystem particularly vulnerable to human-induced alterations.
Keywords: Variação interanual; Censo visual; Assembleia de peixes; Igarapés